Penerapan Program Literasi Pada Mata Pelajaran Pendidikan Agama Islam Di SMAN 4 Palangka Raya - Syar, Nur Inayah; Arifah, Siti Nur; Normuslim, Normuslim (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2021)
This research was conducted based on the Regulation of the Minister of Education and Culture Number 23 of 2015 concerning character development which is implemented in the School Literacy Movement. The purpose of this research is to describe the application of literacy in Islamic Religious Subject, explain information related to supporting factors, and inhibiting factors for the application of literacy at SMAN 4 Palangka Raya. This research is a descriptive qualitative research and the research subjects are teacher and students at SMAN 4 Palangka Raya. The results showed that the application of literacy in SMAN 4 Palangka Raya reached the second stage, namely the reading and writing stages. The application of literacy in SMAN 4 Palangka Raya is not in accordance with the guidelines in the GLN and GLNB manuals. This is because the books that are often used in literacy during PAI subjects are textbooks, whereas the appropriate books should be non-textbooks. The supporting factor for the application of literacy is the ability of teachers to utilize technology and learning media. The servant factors for the application of literacy are the lack of mentoring, the lack of availability of non-text books and the lack of student persistence and interest.